Carbon dioxide adsorption and activation on gallium phosphide surface monitored by ambient pressure x-ray photoelectron spectroscopy. (19th March 2021) - Ye, Yifan; Su, Hongyang; Lee, Kyung-Jae; Larson, David; Valero-Vidal, Carlos; Blum, Monika; Yano, Junko; Crumlin, Ethan J
Abstract: Gallium phosphide (GaP) is a promising catalyst material used in the photo-electrochemical carbon dioxide (CO2 ) reduction reaction (CO2 RR). However, experimental data needed to interpret the interactions between CO2 and GaP at their interfaces must be gathered in order to develop advanced GaP based catalysts for the CO2 RR. Here we used ambient pressure x-ray photoelectron spectroscopy to characterize the surface chemistry at 298 K on the GaP surface exposed to CO2 alone and in the presence of H2 O under both dark and illuminated conditions. We found that a carbonate-like configuration is stable on the GaP surface exposed solely to 0.35 Torr CO2 . Shining solar light promoted the CO2 dissociation process on the surface while negligibly influencing the CO2 adsorption configuration on GaP. Based on the surface chemistry change under dark and illuminated conditions, we propose a CO2 dissociation pathway on GaP. We also found that linear physisorbed CO2 formed on the surface of GaP when 0.35 Torr CO2 is co-dosed with 0.35 Torr H2 O. Co-dosing H2 O with CO2 also created a surface dipole, which is further influenced by solar light illumination. This work provides a fundamental atomic level understanding of how CO2 adsorption and activation happened on the GaP surface and how it was further influenced by solar light.